Implementasi Perlindungan Konsumen bagi Pengguna Shopee PayLater Kalangan Mahasiswa Universitas Negeri Padang - Miranda, Osy; Adnan, M Fachri (Al-DYAS, 2026)
The rise of digital financial services such as Shopee PayLater has gained increasing popularity among university students due to the convenience and flexibility it offers in transactions. However, this ease of access also brings forth a range of consumer protection issues, including lack of transparency in information, potential misuse of personal data, and low consumer awareness of their rights. This study aims to analyze the implementation and influencing factors of consumer protection for Shopee PayLater users among students at Universitas Negeri Padang. A descriptive qualitative approach was employed, with primary data obtained through interviews with student users and lecturers knowledgeable about consumer protection issues, and secondary data sourced from regulations and official documents. Data were analyzed using John F. Kennedy’s theory of basic consumer rights, which includes the right to safety, the right to be informed, the right to choose, and the right to be heard. The findings reveal that the implementation of consumer protection in this context remains suboptimal. Data security systems lack transparency, service information is difficult to access due to complex terms and conditions, consumer choices are often influenced by aggressive promotions, and complaint mechanisms are not adequately responsive. Internal factors affecting consumer protection include low financial literacy and consumerist behavior among students, while external factors involve weak regulation, limited government oversight, and a lack of corporate social responsibility among digital service providers. These findings underscore the importance of synergy between government regulation, ethical business practices, and consumer legal awareness to foster fair and balanced digital transactions.